A Review on Antidiabetic and Antioxidant Potential of Macrotyloma Uniflorum Seed Extract: A Correlative Study of Disease Pathways - Mohd Tahseen,; Shiv Dev Singh, (International Journal of Scientific Research in Science and Technology, 2025)
Macrotyloma uniflorum (horse gram) has emerged as a nutraceutical with promising antidiabetic and antioxidant properties. This review offers a novel integrative analysis of the seed extract's bioactive compounds and their dual role in targeting oxidative stress and dysregulated glucose metabolism—key drivers of diabetes progression. By bridging phytochemistry with metabolic disease pathway, we propose a system biology perspective that highlights the potential of M. uniflorum to act as both therapeutic agent and metabolic modulator. This correlative study not only underscores its pharmacological benefits but also opens avenues for developing multifunctional interventions to prevent diabetes and its oxidative complications.
Keywords: Macrotyloma uniflorum; Oxidative stress; Antioxidant; Antidiabetic; Bioactive Phytoconstituents